Improvement of Game Understanding and Modern Regulation of Pentathlon in 2022 in East Java - Arief Darmawan; Lokananta Teguh Hari Wiguno; Zihan Novita Sari; Tatok Sugiarto; Moh. Fathur Rohman; Linggo Jiventino Yono Prayogo; Ahadi Priyohutomo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Community service activities were held on October 5 and November 3, 2022 with a total number of 75 participants. 40 students and 35 teachers and trainers. this activity was carried out online via zoom and continued with practice in the field of the Faculty of Sports Science, State University of Malang. The purpose of this service is to improve understanding of the rules and games of the Modern Pentathlon sport so that there will be many new young athletes who will be mentored by Physical Education, Sports and Health teachers. The implementation method is divided into four stages, namely: a) Licensing and Approach to PB Modern Pentathlon b) Making materials, c) Preparation for Implementation: Survey of locations for activities, making media. This media was created as a means of disseminating information through electronic media which contains information about the regulations of Modern pentathlon, preparation of socialization, d) Evaluation of activities. The results of this activity indicate an increase in the understanding of teachers, coaches and students about the rules and games of the Modern Pentathlon sport. This is the first time that Indonesia has participated in the Modern Pentathlon at the 2018 Asian Games. This sport continues to show positive developments by becoming the overall champion at the 2019 Philippine sea games. So that it is necessary to socialize and improve the understanding of sports actors, both teachers, coaches and students.